The impact of ease of doing business and technological infrastructure on economic growth in the Arab world - Maiss, Amale El; Taher, Hanadi (Nurture, 2024)
Purpose: This paper examines the effects of technological infrastructure and a business-friendly environment on economic growth in the Arab world from 2004 to 2021 using a detailed panel data analysis approach. Design/Methodology/Approach: The study chooses the fixed effect model based on the Hausman test with additional diagnostic tests confirming the absence of serial correlation and heteroscedasticity employing fixed and random effect models on data from thirteen Arab countries. Findings: Findings reveal a negative relationship between ease of doing business and GDP growth (Gross Domestic Product) suggesting that improvements in the business environment paradoxically decrease economic growth. Conversely, a positive relationship exists between the human development index and economic growth underscoring the significance of human capital. Notably, no significant relationship is detected between technological infrastructure and economic growth. Conclusion: The study concludes that regulatory reforms and human capital investment are pivotal for economic growth in the Arab world challenging the assumed positive impact of ease of doing business on economic expansion. It underscores the need for a strategic focus on developing human resources and technological infrastructure to foster sustainable economic growth. Contribution to the Literature: This research contributes to the economic literature by highlighting the nuanced effects of the ease of doing business and the essential role of human capital in driving economic growth within the Arab region offering new insights for policymakers.